Bunker Cave stalagmites: an archive for central European Holocene climate variability - Fohlmeister, Jens; Schröder-Ritzrau, Andrea; Scholz, Denis; Spötl, Christoph; Riechelmann, Dana; Mudelsee, Manfred; Wackerbarth, Anne Katrin; Gerdes, A.; Riechelmann, S.; Immenhauser, A.; Richter, Detlev K.; Mangini, Augusto (Climate of the past, 2012)
Holocene climate was characterised by variability on multi-centennial to multi-decadal time scales. In central Europe, these fluctuations were most pronounced during winter. Here we present a record of past winter climate variability for the last 10.8 ka based on four speleothems from Bunker Cave, western Germany. Due to its central European location, the cave site is particularly well suited to record changes in precipitation and temperature in response to changes in the North Atlantic realm. We present high-resolution records of δ18O, δ13C values and Mg/Ca ratios. Changes in the Mg/Ca ratio are attributed to past meteoric precipitation variability. The stable C isotope composition of the speleothems most likely reflects changes in vegetation and precipitation, and variations in the δ18O signal are interpreted as variations in meteoric precipitation and temperature. We found cold and dry periods between 8 and 7 ka, 6.5 and 5.5 ka, 4 and 3 ka as well as between 0.7 and 0.2 ka. The proxy signals in the Bunker Cave stalagmites compare well with other isotope records and, thus, seem representative for central European Holocene climate variability. The prominent 8.2 ka event and the Little Ice Age cold events are both recorded in the Bunker Cave record. However, these events show a contrasting relationship between climate and δ18O, which is explained by different causes underlying the two climate anomalies. Whereas the Little Ice Age is attributed to a pronounced negative phase of the North Atlantic Oscillation, the 8.2 ka event was triggered by cooler conditions in the North Atlantic due to a slowdown of the thermohaline circulation.